Bicycling Technique and Related Principle of Spinal Core Stability - Guoqing ZHOU; Huachun QIAN; Hua LI; Xinmiao YAO (康复学报)
Objective:To explore bicycling technique and its connection with spinal core stability.Methods:Core bicycling technique including body positioning technique pedaling technique were discussed based on literature review. Stability mechanism of lumbar vertebrae and cervical vertebrae including collaborative limbs force and levator ani, abdomen, corresponding training effect of body sway on the local stability of muscles were analyzed.Results:Bicycling plays an important role in the prevention and treatment of spinal diseases, and it is one of the effective training to strengthen the stability of spine. Moreover, as a representative aerobic exercise, whole body movement helps to speed up the recovery of spinal disease.Conclusion:The value of bicycling in the prevention and treatment of spinal disease is worth further digging, and the study about bicycling would provide a more open approach to the prevention and treatment of chronic degenerative diseases such as cervical spondylosis and chronic low back pain.